Critical levels and loads and the regulation of industrial emissions in northwest British Columbia, Canada. (December 2016) - Williston, P.; Aherne, J.; Watmough, S.; Marmorek, D.; Hall, A.; de la Cueva Bueno, P.; Murray, C.; Henolson, A.; Laurence, J.A.
Abstract: Northwest British Columbia, Canada, a sparsely populated and largely pristine region, is targeted for rapid industrial growth owing to the modernization of an aluminum smelter and multiple proposed liquefied natural gas (LNG) facilities. Consequently, air quality in this region is expected to undergo considerable changes within the next decade. In concert, the increase in LNG capacity driven by gas production from shale resources across North America has prompted environmental concerns and highlighted the need for science-based management decisions regarding the permitting of air emissions. In this study, an effects-based approach widely-used to support transboundary emissions policy negotiations was used to assess industrial air emissions in the Kitimat and Prince Rupert airsheds under permitted and future potential industrial emissions. Critical levels for vegetation of SO2 and NO2 and critical loads of acidity and nutrient nitrogen for terrestrial and aquatic ecosystems were estimated for both regions and compared with modelled concentration and deposition estimates to identify the potential extent and magnitude of ecosystem impacts. The critical level for SO2 was predicted to be exceeded in an area ranging from 81 to 251 km 2 in the Kitimat airshed owing to emissions from an existing smelter, compared with <1 km 2 in Prince Rupert under the lowest to highest emissions scenarios. In contrast, the NO2 critical level was not exceeded in Kitimat, and ranged from 4.5 to 6 km 2 in Prince Rupert owing to proposed LNG related emissions. Predicted areal exceedance of the critical load of acidity for soil ranged from 1 to 28 km 2 in Kitimat and 4–10 km 2 in Prince Rupert, while the areal exceedance of empirical critical load for nutrient N was predicted to be greater in the Prince Rupert airshed (20–94 km 2 ) than in the Kitimat airshed (1–31 km 2 ). The number of lakes that exceeded the critical load of acidity did not vary greatly across emissions scenarios in the Kitimat (21–23 out of 80 sampled lakes) and Prince Rupert (0 out of 35 sampled lakes) airsheds. While critical loads have been widely used to underpin international emissions reductions of transboundary pollutants, it is clear that they can also play an important role in managing regional air emissions. In the current study, exceedance of critical levels and loads suggests that industrial emissions from the nascent LNG export sector may require careful regulation to avoid environmental impacts. Emissions management from LNG export facilities in other regions should consider critical levels and loads analyses to ensure industrial development is synergistic with ecosystem protection. While recognizing uncertainties in dispersion modelling, critical load estimates, and subsequent effects, the critical levels and loads approach is being used to inform regulatory decisions in British Columbia to prevent impacts that have been well documented in other regions. Highlights: LNG terminals proposed for NW British Columbia may double emissions of NOx and SO2 . Soil critical loads of acidity averaged 181–219 meq m −2 yr −1 . Exceedance in small areas was predicted under worst-case emissions scenarios. Up to 20% of lakes were predicted to exceed critical loads of acidity. Critical levels and loads can inform LNG impact assessment and emissions regulation.